PERANCANGAN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) DI DESA TRIHARJO KECAMATAN GEMUH KABUPATEN KENDAL DENGAN MEMANFAATKAN ALIRAN IRIGASI - Sigit Kurniawan (FTE 16 UMY 027, 2016)
*27 Micro-hydro power plant is a power plant that is clean energy, easy to apply, fast and effective.. The development objective micro hydro power plant on irrigation channels juwero is to harness the potential energy and reworked to produce energy but does not alter the function of the flow of rice field irrigation itself. Planning to use discharge design of 1,266 / s with a high fall effective (net head) of 8.866 m, measures of major inter alia: cross sectional area of the mouth of elbow ( ) 6358 , wide-mouth Elbow ( ) 24 cm, length of pipe 20 m, 0.9 m diameter pipe can be utilized to build hydroelectric power plants with a power turbine ( ) 66 kW, rotation turbine 298 rpm, the power generator ( ) 56 kw, and the rotation generator ( ) 1500 rpm. Keywords : Turbine, Power, Round of, Generator